Critical Questions Related to the Influence of Academic Advising on Student Success: Setting a Research Agenda - Wendy Troxel (Academic Chairpersons Conference Proceedings, 2017)
Academic leaders, faculty, and academic advisers are uniquely positioned to describe complex scenarios related to student success that need further systematic examination and analysis. This highly interactive session will engage participants in a brainstorming and consensus-building activity to generate a list of "critical questions" in related to the relationship between academic advising and student success that leads to meaningful research across disciplinary contexts and partnerships. The resulting document will be useful to faculty and staff who desire to engage in research that will inform the scholarship of advising and implications for advising practice in all levels of higher education.
Keywords: critical questions; academic advising; higher education